375 Paediatric Abdominal Pain: A Call for a Bayesian Approach to Decision Making. (October 2012) - Beardsley, C; Dillon, A; Chiu, M; Shaw, R; Croaker, D
Abstract : Background/aim of study: Paediatric abdominal pain is a common. Efficient investigation and triage remains a challenge with stubborn rates of negative appendicectomy. This study analysed the characteristics of paediatric presentations with abdominal pain. Methods: Retrospective review of presentations to casualty with abdominal pain in calendar years 2005–2006. Data was collected on age, sex, time of presentation, investigations and outcomes. Main results 1. 1007 patients presented with abdominal pain with a female preponderance. A peak in incidence about the age of 6–7 in both sexes was noted. The incidence in both sexes then stabilised till a pubertal rise in female incidence. There is a seasonal variation with approx 25% more pain presentations in winter. No such seasonal effect was seen for appendicitis. Overall abdominal pain is more likely to present after midday, while appendicitis presents throughout the day. 81 of 1007 patients had appendicectomies, 61 with appendicitis. Adolescent females were much more likely to have normal appendixes removed, with p<0.001. 2. Mean WCC was 15.1 for those with true appendicitis, compared to 11.4 for those with normal appendices: WCC sensitivity 87% and specificity 90%. In those who had ultrasound, the appendiceal visualisation rate was 57%. Conclusion: Paediatric abdominal pain presentations vary in incidence depending on sex, age, season and time of day. Conditions requiring operation are relatively uncommon, and the patient's background, history and a priori likelihood of disease should be considered before ordering investigations or operation.